2016
DOI: 10.3945/ajcn.116.137208
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the reliability of glycemic index values and potential sources of methodological and biological variability

Abstract: Background: The utility of glycemic index (GI) values for chronic disease risk management remains controversial. Although absolute GI value determinations for individual foods have been shown to vary significantly in individuals with diabetes, there is a dearth of data on the reliability of GI value determinations and potential sources of variability among healthy adults. Objective: We examined the intra-and inter-individual variability in glycemic response to a single food challenge and methodologic and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 43 publications
3
80
1
6
Order By: Relevance
“…Matthan et al studied the glycemic response to a single food item in 63 healthy volunteers, and found substantial variability in their responses (20% within an individual and 25% between individuals) [86]. The authors suggest that the high degree of variability in glycemic response means that GI is unlikely to be a good method to inform food choices.…”
Section: Replacement Of Sfa With N-3 Pufamentioning
confidence: 99%
“…Matthan et al studied the glycemic response to a single food item in 63 healthy volunteers, and found substantial variability in their responses (20% within an individual and 25% between individuals) [86]. The authors suggest that the high degree of variability in glycemic response means that GI is unlikely to be a good method to inform food choices.…”
Section: Replacement Of Sfa With N-3 Pufamentioning
confidence: 99%
“…Diversos estudios han informado que los alimentos con elevados valores de IG y CG se han relacionado con un mayor riesgo de diabetes (11,12), pero otros reportes no han confirmado estos resultados. Como estrategia para ayudar a mantener la euglicemia en el diabético, existen suplementos nutricionales específicos para diabetes utilizados como sustitutos calóricos nutritivos en individuos normopesos, con sobrepeso u obesos; o suplementos para desnutridos con diabetes mellitus tipo 2 (DM2) (13). La mayoría de estos productos diseñados con el fin de elongar la respuesta glicémica han sido edulcorados con distintos tipos de endulzantes.…”
Section: Introductionunclassified
“…In a recent article, Matthan et al (1) measured glucose and insulin responses elicited by 50-g available carbohydrate portions of white bread and glucose in 63 subjects. They concluded that the substantial variability in individual responses to glycemic index (GI) value determinations makes GI an unreliable approach to guiding food choices.…”
mentioning
confidence: 99%
“…Matthan et al (1) reported that the mean 6 SD GI of Pepperidge Farm Original White Bread was 62.4 6 15.3, and they consider this amount of variation to be substantial enough to show that GI should not be used to guide food choices because of the potential to misclassify foods as low (GI 55), medium (56-69), or high (GI $70) GI. However, this interpretation is incorrect.…”
mentioning
confidence: 99%